Optimum Work Frequency for Marine Monitoring Based on Genetic Algorithm - Fahraini Bacharuddin; Hadi Wuryanto; Yuliza Yuliza; Beny Nugraha (Universitas Ahmad Dahlan, 2018)
The communication using of HF (High Frequency) is a system that depends on wave propagation using sky waves reflected by the earth's ionosphere layer so that it is highly effective for long distance communication, but highly dependent on varying ionospheric conditions from day and night (time after time) as well as the location of the transmitter and receiver radio. Currently, there is only one main frequency channel and one reserve frequency channel so that there are frequency constraints unable to communicate due to ionosphere changes. This research will predicted allocation of HF frequency to support long distance communication for marine monitoring using Genetic Algorithm method. Output or prediction results in the form of Optimum Work Frequency (OWF) for 24 hours and frequency graph.